Prevalence of anemia among school girl children and effectiveness of supplementation intervention - Murthy, H. M. Keshava; Murthy, Tanishka K.; Nath, Amol (International Journal Of Community Medicine And Public Health, 2021)
Background: Iron deficiency anemia (IDA) is a major public health issue worldwide, especially in developing countries. Anemia prevalence in young children, particularly girls, continues to remain high in most parts of India and Asia. Aims and objectives were to study the prevalence of anemia (IDA) among school girl children of age group between 5-16 years and to assess the effectiveness of iron-folic acid supplements and iron rich diet. Methods: The study was conducted among 558 school girls in the age group between 5-16 years (1st to 10th standard) at a Kendriya Vidyalaya in Punjab. The study group was checked for their hemoglobin level. Health education regarding prevention of anemia was imparted to girls and their parents followed by daily iron-folic acid supplement. Their hemoglobin was again checked after three months of supplementation. Results: The prevalence of anemia in the study group was 65%. After the intervention, the Hb level was significantly increased as shown by increase in mean and SD of Hb% from 9.75±1.24 to 11.66±0.98. The data was analyzed in two age groups, 5-10 years and 11-16 years, to check for any significant variation in their Hb levels. Though there was difference in prevalence of anemia in these age groups, the difference was not statistically significant. Conclusions: The study showed that prevalence of anemia is 65% and is still one of the major public health issues among school going girl children of all age. In addition to pre-school and adolescent girls, we also need to focus on pre-puberty girls, as anemia is equally prevalent among them.